2015
DOI: 10.1111/itor.12209
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic algorithm for optimal location of flow‐refueling capacitated stations

Abstract: Constructing refueling stations in the transportation network is one of the most important steps toward the promotion of alternative-fuel vehicles. The capacity of these stations is usually limited. In this paper, a new capacitated refueling station location model and a solution algorithm are proposed. The algorithm is divided into two main steps. At first step, a restricted capacitated problem on core sets is constructed. Then, a modified Lagrangean iterative method is used for obtaining solutions. The Lagran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Limited charging station capacities were considered e.g. in [45] and [19]. The possibility of using paths slightly deviating from the shortest origin-destination paths was studied by Kim and Kuby [27], [28], Yildiz et al [52] and Li et al [31].…”
Section: Modeling the Ev Station Location Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited charging station capacities were considered e.g. in [45] and [19]. The possibility of using paths slightly deviating from the shortest origin-destination paths was studied by Kim and Kuby [27], [28], Yildiz et al [52] and Li et al [31].…”
Section: Modeling the Ev Station Location Problemmentioning
confidence: 99%
“…Lee and Han [30] formulated the flow refueling location problem under a stochastic driving range as a MINLP and proposed a Benders-and-Price algorithm (BD&P) combining Benders decomposition and column generation techniques to solve their problem. Hosseini and MirHassani [19] investigated the problem with capacitated refueling stations and developed a heuristic solution method based on the Lagrangian relaxation (LGR) of the capacity constraints.…”
Section: Solving the Flow Refueling Location Problemmentioning
confidence: 99%
“…Extensions of the basic problem taking into account a limited charging capacity of the stations (see e.g. [8] and [21]) or the possibility of using paths slightly deviating from the shortest origin-destination path (see e.g. [10], [14], [18] and [25]) were also considered.…”
Section: Position In the Literaturementioning
confidence: 99%
“…Constraints (16) state that if a trip q has a strictly positive probability of coverage (z q > 0), for each node l ∈ N q \ {O q }, there must exist a node k visited before l during trip q, where the vehicle can be refueled up to node l. Constraints (17) link the coverage probability variables z q to the binary variables w kl q . They state that variable z q is calculated as the smallest coverage probability over all segments [k, l] where node l is refueled by a station at node k. Constraints (3), (5), (6) and (8) are maintained from the deterministic formulation FRLM2.…”
Section: Expected Flow Refueling Location Model (Efrlm)mentioning
confidence: 99%
“…This indicates that timely refueling on the road is one of the most fundamental reasonable location problem of gas stations, the core of which is the construction and evaluation of gas station location models, which are typically analyzed and evaluated based on Geography Information System (GIS) spatial analysis and the actual demand for vehicle refueling [18]. For example, based on different route choices and traveling conditions, Hosseini [19] and Miralinaghi [20] studied the construction methods of a gas station location model, as well as its heuristic algorithm, and finally showed that GIS spatial analysis can be used to scientifically optimize the location of gas stations. In Field (3), the major research is concerned with scientific scheduling and routing optimization for mobile refueling facilities, such as airport tankers, space refueling aircraft, etc.…”
Section: Motivationmentioning
confidence: 99%